(untitled) (The South East European Journal of Economics and Business, 2022)
This paper seeks to examine the determinants of the profitability of the B&H banking sector, using an empirical framework that incorporates the traditional SCP - structure conduct-performance and ESX efficiency hypothesis. The main goal of this paper is to measure the level of concentration and investigate how concentration and other determinants influence the profitability of the banking sector in Bosnia and Herzegovina for the period from 2008 to 2017. We also tried to determine whether the profitability of the banking sector is more contributed by concentration, i.e. enlargement of the banking market (SCP) rather than increased efficiency of banking organization (ESX). For this purpose, we use a sample of 26 banks from B&H, and our empirical research is based on panel data analysis. The performance of the banking sector is measured by the conventional return on assets (ROA). Besides concentration as a main industry-specific factor, profitability determinants include bank-specific and macroeconomic profitability factors. Obtained results reveal that concentration has positive impacts on B&H banking profitability. But when we talk about competing concentration hypotheses, the paper results here generally support the ESX efficiency hypothesis rather than the traditional SCP approach. It was confirmed that credit risk, deposit risk and cost to income ratio from bank-specific variables, and GDP growth rate from macroeconomic variables have a statistically significant influence on banking performance.